FAKTOR- FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PADA PEKERJA DENGAN HAZARD KIMIA DI DALAM RUANG TERBATAS DI PT Z - Promisetyaningrum Fitria Nurani; Ida Wahyuni; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Each worker is faced to various risks that may cause interference to occupational safety and health. One of the health problems which has less attention from the company is work stress. Work stress can occur with certain working conditions, such as noise, acidic, and contained hydrogen fluoride gases and the work done inside confined space. The purpose of this research was to determine factors related work stress on workers with chemical hazard in confined spaces in PT Z. This type of research is explanatory research with cross sectional design. A total of 30 samples taken from the total population. The results of the study described that 60% of respondents had high work stress and 40% of respondents had low work stress. Based on bivariate analysis with a significance level of 5% known that there are six factors related to work stress such as age with p-value of 0.000, the level of education with a p-value of 0.001, marital status with a p-value of 0.006, working period with a p-value of 0.049, the workload physical with p-value of 0.000, hydrogen fluoride gases with a p-value of 0.003. Work stress in the confined space could be minimized by company with increasing the number of blower to reduce hydrogen fluoride gasesand and the temperature in the tank fitted to the standard and checked the worker PPE periodically, especially on the properness of a reusable filter respirator mask.